Composite metal oxide solid base catalyst and application thereof in vanillin synthesis

Through the application of composite metal oxide solid base catalyst, the problems of high catalyst price and low selectivity in vanillol synthesis are solved, and efficient and low-cost vanillol production is achieved, and the catalyst has good cyclicity and selectivity. .

CN119186575AInactive Publication Date: 2024-12-27TIANJIN VOCATIONAL INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411317895.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The catalysts in the existing vanillol synthesis process are expensive and have low selectivity, which limits industrial applications.

Method used

The composite metal oxide solid base catalyst is used to combine amphoteric metal oxide copper oxide with common rare earth metal oxides. It is used for the hydroxymethylation reaction of guaiacol and formaldehyde to provide synergistic catalytic action and enhance vanillol selectivity and productivity.

Benefits of technology

The efficient catalytic synthesis of vanillol is achieved, which reduces raw material costs, improves selectivity and production efficiency, and the catalyst is easy to be separated and recycled.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite metal oxide solid base catalyst and application thereof in vanillin synthesis. The specific surface area of the composite metal oxide solid base catalyst is 10-50m < 2 > / g; the acidity function H <-> is 9.3-15; the chemical composition is RexOy.nCuO, n is equal to 1-10, x is equal to 1-2, and y is equal to 2-3; the catalyst is formed by compounding amphoteric metal oxide copper oxide and common rare-earth metal oxide, and the common rare-earth metal oxide is one of La2O3, CeO2, Tb2O3, Dy2O3, Y2O3, Eu2O3 and Nd2O3 and can be used as an efficient catalyst for catalytic synthesis of vanillyl alcohol through reaction of guaiacol and formaldehyde. The rare earth metal oxide solid alkali and the amphoteric metal oxide CuO solid alkali are compounded, and the catalytic performance of the catalyst is superior to that of the existing inorganic alkali and organic alkali under the synergistic catalysis of the two metal oxides; the vanillin alcohol is prepared through catalysis of the composite metal oxide solid base, and the method has the advantages of being simple in process, high in selectivity, wide in raw material source and low in raw material cost and is a novel green process for synthesizing the vanillin alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite metal oxide solid base catalyst and application thereof in the synthesis of vanillin alcohol, belonging to the technical field of catalytic materials and organic synthesis. Background Art

[0002] The chemical name of vanillin is 4-hydroxy-3-methoxybenzyl alcohol. It is mainly used as a flavor and fragrance for food and cosmetics, a thermosensitizer and a pharmaceutical intermediate. It is mainly prepared by reducing vanillin.

[0003] Patent CN113262797B (2022-12-27) discloses a nickel-based catalyst, a preparation method, and its application in the hydrogenation of vanillin to synthesize vanillin alcohol. Due to the high cost of raw material vanillin, raw material reducing agent, and catalyst, the industrial application of this route is limited. It is urgent to research and develop a low-cost green synthesis process route for vanillin alcohol.

[0004] In the early days, a Japanese company disclosed a method for preparing vanillic alcohol by hydroxymethylating phenolic compounds in European Patent EP0485613B1 (1995-06-12). The organic quaternary ammonium base was used to replace the conventional inorganic base, which greatly improved the selectivity of synthesizing vanillic alcohol. However, the quaternary ammonium base was expensive, so the method was limited to experimental research.

[0005] The French company disclosed a method for hydroxyalkylation of carbocyclic aromatic ethers in Chinese patent CN1169766C (2004-10-06), using a zeolite solid base catalyst to first synthesize vanillin alcohol, which was further oxidized to vanillin. When the conversion rate of the raw material guaiacol was 73%, the selectivity of generating 3-methoxy-4-hydroxybenzyl alcohol was 49%. Professional and technical personnel were inspired to use a solid base catalyst to improve the selectivity of generating vanillin alcohol from the hydroxymethyl group of phenolic compounds.

[0006] Patent CN101486630B (2013-06-12) discloses a method for catalytically synthesizing 3-methoxy-4-hydroxybenzyl alcohol. The method uses guaiacol and formaldehyde as raw materials and ethanolamine or diethylamine as a catalyst to improve the selectivity of synthesizing 3-methoxy-4-hydroxybenzyl alcohol and reduce the cost of raw materials. In the embodiments, the selectivity of the catalytic synthesis of vanillyl alcohol is even lower than that of using sodium hydroxide or potassium hydroxide catalyst.

[0007] Patent CN114988990B (2023-12-19) discloses a method for preparing vanillin, comprising: (1) mixing guaiacol, formaldehyde, alkali, and water to undergo a condensation reaction to obtain a condensation reaction liquid containing 3-methoxy-4-hydroxy-benzyl alcohol; (2) adding a platinum-carbon catalyst (Pt / C) and an auxiliary agent to the condensation reaction liquid of step (1), and then introducing an oxygen-containing gas to cause 3-methoxy-4-hydroxy-benzyl alcohol to undergo an oxidation reaction to produce vanillin. In the example, the raw material conversion rate is 99.5%, and the selectivity of 3-methoxy-4-hydroxy-benzyl alcohol is as high as 92.9%, but the experimental results in the example of the patent cannot be repeated or are difficult to experimentally confirm.

[0008] In view of the above problems, the present invention is proposed. Summary of the invention

[0009] In view of the shortcomings of the prior art, the first purpose of the present invention is to provide a composite metal oxide solid base catalyst to overcome the defects of the existing vanillin alcohol synthesis process, such as high catalyst price and low selectivity.

[0010] The second object of the present invention is to provide a method for preparing the composite metal oxide solid base catalyst.

[0011] The third object of the present invention is to provide the use of the composite metal oxide solid base catalyst in the synthesis of vanillic alcohol.

[0012] In order to achieve the first purpose, the present invention is implemented by the following technical scheme: a composite metal oxide solid base catalyst, the specific surface area of ​​the composite metal oxide solid base catalyst is 10-50m 2 / g; acid function H - is 9.3-15; the chemical composition is Re x O y ·nCuO, wherein n=1-10, x=1-2, y=2-3; the composite metal oxide solid base catalyst is composited by amphoteric metal oxide copper oxide and common rare earth metal oxide, wherein the common rare earth metal oxide is one of lanthanum oxide (La2O3), cerium dioxide (CeO2), terbium oxide (Tb2O3), dysprosium oxide (Dy2O)3, yttrium oxide Y2O3, europium oxide (Eu2O3), and praseodymium oxide (Nd2O3), and can be used as a high-efficiency catalyst for catalyzing the synthesis of vanillin alcohol by the reaction of guaiacol and formaldehyde.

[0013] According to the generalized acid-base theory, the solid base is a solid compound that can accept protons or provide electron pairs, and the solid base includes metal oxides, molecular sieves, loaded alkali metals, clay minerals, alkali metal fluorides and alkaline ion exchange resins, etc. Metal oxides are an important type of solid base.

[0014] Composite metal oxide solid base can provide a more favorable multiphase catalytic environment than liquid base, and catalyzes reactions that are difficult to carry out efficiently in the liquid phase. Solid base catalysts are non-corrosive and do not require neutralization of the reaction liquid after the catalytic reaction is completed. Solid base catalysts can be directly separated, recovered, and recycled.

[0015] Preferably, the composite metal oxide solid base catalyst in the present invention is different from the inorganic and organic soluble base catalysts in the prior art. The catalytic reaction is carried out on the surface of the composite metal oxide solid base catalyst instead of in the solution. The composite metal oxide solid base catalyst can only accelerate the hydroxymethylation reaction of guaiacol and formaldehyde on the catalyst surface, and will not accelerate the phenolic polymerization side reaction of guaiacol and formaldehyde in the reaction solution.

[0016] Preferably, the CuO in the composite metal oxide solid base catalyst of the present invention is an amphoteric metal oxide, the copper atoms in the CuO molecules can provide electron pairs, and the surface can produce acidic sites; while the oxygen atoms can accept protons, and the surface can produce basic sites; the basic sites and acidic sites in the CuO molecules have a synergistic catalytic effect on certain chemical reactions.

[0017] Preferably, the rare earth metal oxide in the composite metal oxide solid base catalyst of the present invention has a strong alkalinity on its surface, but its specific surface area is relatively small, which affects the performance of its strong alkalinity on the surface. x O y Composited with amphoteric metal oxide CuO, it expands the Re x O y The specific surface area and the synergistic catalytic effect of the two metal oxides greatly improve the catalytic performance of the composite metal oxide solid base.

[0018] The catalytic mechanism of composite metal oxide solid base catalysts is still unclear. The research on solid base catalysts is generally carried out on the basis of solution acid-base chemistry. The alkalinity of solid bases is usually measured by the acid function H. - express.

[0019] Acid function H - Defined as the ability of an alkaline solution to abstract a proton from an acidic neutral solute AH.

[0020] H - =pKa-lg([AH] / [A - ])

[0021] To determine the H of a solution - Values, AH and A must be accurately determined - When half of the solute AH in the solution is deprotonated, that is, [AH] = [A - ], H- The value is equal to the pKa value of AH.

[0022] If the pKa value of the neutral molecule whose proton is extracted is larger, it means that the alkalinity of the solution is stronger. For example, the H-value of 5.0 mol / L NaOH aqueous solution at room temperature is 15.2; for methanol solution, the H-value of 3.0 mol / L NaOCH3 is 18.3.

[0023] H can also be used - The value is used to describe the base strength of solid base catalysts. Assuming an indicator molecule AH, with surface basic site B - effect:

[0024] AH+B - →A - +BH

[0025] Surface basicity B - H - The value is defined as: H - =pKa-lg([AH] s / [A - ] s )

[0026] Here [AH] s and [A - ] s AH and A are the solid surface - concentration.

[0027] After the solid surface adsorbs AH from the solution, if [AH] s / [A - ] s >>1, the solid shows the color of AH, and when [AH] s / [A - ] s <<1, solid display A - of color; and when [AH] s / [A - ] s =1, H at the basic site on the surface - The value is equal to the pKa of indicator AH.

[0028] For the base-catalyzed reaction of guaiacol and formaldehyde, the greater the alkalinity, the better the catalytic effect. It is important to choose a base catalyst with appropriate alkalinity. The experiment found that Re x O y Acidity Function H of CuO Composite Metal Oxide Solid Base Catalyst - It is 9.3-15, which is in the optimized range.

[0029] In order to achieve the second object, the present invention is implemented by the following technical scheme: a preparation method of a composite metal oxide solid base catalyst, comprising the following preparation steps:

[0030] S1: Mix a 2 mol / L soluble copper salt aqueous solution and a soluble salt aqueous solution of a rare earth metal at a molar ratio of Re:Cu=1:1-10; the soluble copper salt is copper nitrate, copper chloride or copper acetate; the soluble rare earth metal salt is one of the nitrate, hydrochloride or acetate of La, Ce, Tb, Dy, Y, Eu or Nd;

[0031] S2: adding 2-5 mol / L ammonia water to the mixed aqueous solution of soluble salts obtained in step S1 under stirring at room temperature to convert the soluble metal salts into a co-precipitation of hydroxides and oxides of copper metal and rare earth metal;

[0032] S3: Separate the coprecipitate of metal hydroxide and oxide, wash with deionized water to remove the salt mixed in the coprecipitate of metal hydroxide and oxide, dry at 110-150°C, and then calcine and activate at 350-550°C for 0.5-2h to obtain a composite metal oxide solid base catalyst with a specific surface area of ​​10-50m 2 / g; acid function H - =9.3-15; chemical composition is Re x O y nCuO, n=1-10, x=1-2, y=2-3; based on Re, the molar yield of the preparation process is 95%-99%.

[0033] In the present invention, the copper oxide and the rare earth oxide are uniformly mixed by coprecipitation so that the two metal oxides produce a synergistic catalytic effect. First, a soluble metal salt aqueous solution of rare earth elements and copper elements is prepared, and then the soluble metal salt aqueous solution is converted into a metal hydroxide or a hydrated oxide under alkaline conditions. Because when the temperature of the reaction solution is high and the alkalinity of the reaction solution is strong, the metal hydroxide is partially dehydrated to form a hydrated oxide of the metal, and the metal hydroxide and hydrated oxide are precipitated and dried and then completely converted into metal oxides. The water absorbed by the metal oxide affects its alkalinity, and high-temperature roasting is required to remove the absorbed water to obtain a composite metal oxide solid base.

[0034] In order to achieve the third object, the present invention is implemented by the following technical scheme: a method for applying a composite metal oxide solid base catalyst in the synthesis of vanillin alcohol, comprising the following steps:

[0035] T1: adding 90%-95% ethanol solvent, raw material guaiacol and composite metal oxide solid base catalyst to the reactor respectively, controlling the mass of raw material guaiacol to be 5%-15% of the mass of ethanol solvent, so that raw material guaiacol and product vanillic alcohol can be completely dissolved at room temperature; controlling the mass of composite solid base catalyst to be 70%-150% of the mass of raw material guaiacol;

[0036] T2: heating the reaction liquid to 60-79° C., adding a 37% formaldehyde aqueous solution under stirring, and controlling the feeding molar ratio to be: guaiacol: formaldehyde = 1: 0.9-1.2, so that guaiacol and formaldehyde are adsorbed on the surface of the composite solid base catalyst for hydroxymethylation reaction to generate 3-methoxy-4-hydroxybenzyl alcohol product and other by-products;

[0037] T3: Keep the reaction warm for 2-6 hours. When the conversion rate of guaiacol in the reaction solution is greater than 95%, cool the reaction solution to room temperature, separate and recover the composite metal oxide solid base catalyst, wash the composite solid base catalyst with ethanol solvent, dry it at 110-150°C, and roast it at 350-550°C before recycling it;

[0038] T4: vacuum distill the reaction liquid to recover 70%-90% of the volume of ethanol solvent for recycling;

[0039] T5: cooling the distillation residue to 5-10°C, separating and crystallizing the crude vanillin alcohol product;

[0040] T6: distilling the crude vanillic alcohol product under a vacuum degree of 1-3 mmHg to obtain a white refined vanillic alcohol product with a liquid chromatography content of 99.5%. The molar yield of the synthesis process is 60%-70% based on the guaiacol raw material.

[0041] Preferably, the reaction temperature is selected to be 60-79° C. to ensure that the hydroxymethylation reaction of guaiacol and formaldehyde can proceed at a faster reaction speed under weak alkaline conditions.

[0042] In the present invention, the molar ratio of guaiacol and formaldehyde raw materials is selected to be close to the chemical reaction stoichiometric ratio to prevent the phenolic polymerization side reaction caused by excessive formaldehyde.

[0043] By adopting the above technical scheme, a larger amount of composite metal oxide solid base catalyst is selected in the present invention, mainly to fully utilize the catalytic surface of the composite metal oxide solid base catalyst, because the hydroxymethylation reaction of guaiacol and formaldehyde compound is mainly carried out on the surface of the composite metal oxide, rather than in the reaction solution.

[0044] The CuO amphoteric metal oxide in the present invention can provide both electron pairs and protons, and the basic sites and acidic sites in the CuO molecules have a synergistic catalytic effect, catalyzing the hydroxymethylation reaction of guaiacol and formaldehyde to generate 3-methoxy-4-hydroxybenzyl alcohol, 3-methoxy-2-hydroxybenzyl alcohol and 3-methoxy-2-hydroxy-p-terephthalylated alcohol and a small amount of phenolic polymer.

[0045] The amphoteric metal oxide CuO in the present invention has different catalytic performance from the zeolite in the prior art. The weak alkalinity of the surface of CuO can not only catalyze the hydroxymethylation reaction of the raw materials guaiacol and formaldehyde, but also make the hydroxymethylation reaction mainly proceed at the para position of the phenolic hydroxyl group, thereby improving the selectivity of generating 3-methoxy-4-hydroxy-benzyl alcohol.

[0046] In the early literature, although there are reports on the synthesis of vanillin alcohol by chloromethylation reaction using cupric chloride or cuprous chloride catalyst, there are no reports on the preparation of vanillin alcohol by using rare earth oxides or composite metal oxides. The applicant found in the green synthesis experiment of vanillin alcohol that CuO solid base has high catalytic activity and selectivity for the hydroxymethylation reaction of guaiacol and formaldehyde, and the basic and acidic sites in the CuO molecule have a synergistic catalytic effect on the hydroxymethylation reaction of guaiacol and formaldehyde. The rare earth metal oxide solid base strengthens this catalytic effect, overcomes the shortcomings of low catalytic efficiency and high corrosiveness of copper chloride, and has outstanding substantial characteristics and significant technical progress.

[0047] The solubility of the raw material guaiacol and the product vanillic alcohol in water at room temperature is very low, but the solubility in ethanol is very high. In order to increase the solubility of guaiacol and the product vanillic alcohol in the reaction solution, the present invention selects an ethanol aqueous solution with a mass concentration of 90%-95% as the reaction solvent, and after the reaction is completed, vacuum distillation is performed to remove part of the ethanol solvent to reduce the solubility of the product, thereby improving the yield of the crude vanillic alcohol product.

[0048] The boiling point of vanillin alcohol at normal pressure is about 300°C. Under a high vacuum of 1-3 mmHg, the boiling point drops to about 175°C. It can be easily separated from by-products and polymer impurities by distillation to obtain a high-purity vanillin alcohol product.

[0049] Beneficial effects of the present invention:

[0050] (1) The present invention combines a rare earth metal oxide solid base with an amphoteric metal oxide CuO solid base, so that the two metal oxides play a synergistic catalytic role, and the catalytic performance is better than that of existing inorganic bases and organic bases.

[0051] (2) The composite metal oxide solid base preparation method of the present invention is simple, easy to separate and recover, and can be recycled.

[0052] (3) The composite metal oxide solid base catalyzed preparation of vanillic alcohol has high selectivity, wide raw material sources and low raw material costs. DETAILED DESCRIPTION

[0053] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0054] Example 1 Synthesis of La2O3-CuO Composite Metal Oxide Solid Base Catalyst

[0055] 100 mL of 2 mol / L lanthanum nitrate aqueous solution and 100 mL of 2 mol / L copper nitrate aqueous solution were mixed under stirring at room temperature, and 100 mL of 5 mol / L ammonia water was added to the mixed aqueous solution to convert the two metal ions in the mixed aqueous solution into a coprecipitation of lanthanum hydroxide and copper oxide. The coprecipitation of lanthanum hydroxide and copper oxide was separated by vacuum filtration, washed with deionized water to remove the ammonium nitrate salt mixed in the coprecipitation, dried at 110-150°C, and then calcined and activated at 550°C for 0.5h to obtain a La2O3-CuO composite metal oxide solid base catalyst, and its specific surface area was measured to be 50m 2 / g; acid function H - is 15; the chemical composition is La2O3·CuO; based on La, the molar yield of the La2O3-CuO composite metal oxide solid base catalyst preparation process is 99%.

[0056] Example 2 Synthesis of CeO2-5CuO Composite Metal Oxide Solid Base Catalyst

[0057] 50 mL of 2 mol / L cerium nitrate aqueous solution and 250 mL of 2 mol / L copper nitrate aqueous solution were mixed under stirring at room temperature, and 280 mL of 5 mol / L ammonia water was added to the mixed aqueous solution to convert the two metal ions in the mixed aqueous solution into a coprecipitation of cerium hydroxide and copper oxide. The coprecipitation of cerium hydroxide and copper oxide was separated by vacuum filtration, washed with deionized water to remove the ammonium nitrate salt mixed in the coprecipitation, dried at 110-150°C, and then calcined and activated at 450°C for 1h to obtain a CeO2-CuO composite metal oxide solid base catalyst, and its specific surface area was measured to be 30m 2 / g; acid function H - is 12.2; the chemical composition is CeO2·5CuO; based on Ce, the molar yield of the preparation process of CeO2-CuO composite metal oxide solid base catalyst is 97%.

[0058] Example 3 Synthesis of Tb2O3-CuO Composite Metal Oxide Solid Base Catalyst

[0059] 25 mL of 2 mol / L terbium nitrate aqueous solution and 250 mL of 2 mol / L copper nitrate aqueous solution were mixed under stirring at room temperature, and 212 mL of 5 mol / L ammonia water was added to the mixed aqueous solution to convert the two metal ions in the mixed aqueous solution into a coprecipitation of terbium hydroxide and copper oxide. The coprecipitate was separated by vacuum filtration, washed with deionized water to remove the ammonium nitrate salt mixed in the coprecipitate, dried at 110-150°C, and then calcined and activated at 350°C for 1h to obtain a CeO2-CuO composite metal oxide solid base catalyst, and its specific surface area was measured to be 10m 2 / g; Acidity function H in ethanol aqueous solution - is 9.3; the chemical composition is Tb2O3·5CuO; based on Tb, the molar yield of the Tb2O3-CuO composite metal oxide solid base catalyst preparation process is 95%.

[0060] Example 4 Synthesis of Vanillyl Alcohol Using La2O3-CuO Composite Metal Oxide Solid Base Catalyst

[0061] 100 g of ethanol solvent with a mass concentration of 90%-95%, 12.4 g (0.1 mol) of guaiacol as a raw material and 24 g of La2O3-CuO composite metal oxide solid base catalyst prepared in Example 1 were added to the reactor respectively; the reaction solution was heated to 60°C, and 9.7 g (0.12 mol) of formaldehyde aqueous solution with a mass concentration of 37% was added under stirring; the reaction was kept warm for 4 hours, and the conversion rate of guaiacol in the reaction solution reached more than 95%, the reaction solution was cooled to room temperature, the composite solid base catalyst was separated and recovered, and ethyl acetate was used to separate and recover the composite solid base catalyst. The reaction mixture was washed with an alcohol solvent, dried at 110-150°C, and further calcined at 550°C to obtain 22g of La2O3-CuO composite solid base catalyst; the reaction liquid was vacuum distilled to recover the ethanol solvent for recycling; the distillation residue was cooled to 5°C, and 12g of crude vanillin alcohol product crystals were separated; the crude vanillin alcohol product was distilled at a vacuum degree of 1-3mmHg to obtain 10.8g of white refined vanillin alcohol product with a liquid chromatography content of 99.5%. The molar yield of the synthesis process was 70% based on the guaiacol raw material.

[0062] Example 5 Synthesis of Vanillyl Alcohol Using CeO2-CuO Composite Metal Oxide Solid Base Catalyst

[0063] 100 g of 90%-95% ethanol solvent, 12.4 g (0.1 mol) of guaiacol as a raw material, and 24 g of CeO2-CuO composite metal oxide solid base catalyst prepared in Example 2 were added to the reactor respectively; the reaction solution was heated to 70° C., and 8.1 g (0.10 mol) of 37% formaldehyde aqueous solution was added under stirring; the reaction was kept warm for 2 h, and the conversion rate of guaiacol in the reaction solution reached more than 95%, the reaction solution was cooled to room temperature, the composite solid base catalyst was separated and recovered, and ethanol was used to The reaction mixture was washed with solvent, dried at 110-150°C, and further calcined at 450°C to obtain 22.5g of CeO2-CuO composite solid base catalyst; the reaction liquid was vacuum distilled to recover the ethanol solvent for recycling; the distillation residue was cooled to 10°C, and 12g of crude vanillin alcohol product crystals were separated; the crude vanillin alcohol product was distilled at a vacuum degree of 1-3mmHg to obtain 10.0g of white refined vanillin alcohol product with a liquid chromatography content of 99.5%. The molar yield of the synthesis process was 65% based on the guaiacol raw material.

[0064] Example 6 Synthesis of Vanillyl Alcohol Using Tb2O3-CuO Composite Metal Oxide Solid Base Catalyst

[0065] 100 g of 90%-95% ethanol solvent, 12.4 g (0.1 mol) of guaiacol as a raw material, and 24 g of the Tb2O3-CuO composite metal oxide solid base catalyst prepared in Example 3 were added to the reactor respectively; the reaction solution was heated to 75° C., and 8.2 g (0.1 mol) of 37% formaldehyde aqueous solution was added under stirring; the reaction was kept warm for 2 h, and the conversion rate of guaiacol in the reaction solution reached more than 95%, the reaction solution was cooled to room temperature, the composite solid base catalyst was separated and recovered, and ethanol was used to The reaction mixture was washed with solvent, dried at 110-150°C, and further calcined at 350°C to obtain 23g of Tb2O3-CuO composite solid base catalyst; the reaction liquid was vacuum distilled to recover the ethanol solvent for recycling; the distillation residue was cooled to 10°C, and 10.2g of crude vanillin alcohol product crystals were separated; the crude vanillin alcohol product was distilled at a vacuum degree of 1-3mmHg to obtain 9.3g of white refined vanillin alcohol product with a liquid chromatography content of 99.5%. The molar yield of the synthesis process was 60% based on the guaiacol raw material.

[0066] Comparative Example 1: Synthesis of Vanillyl Alcohol Using Sodium Hydroxide Liquid Alkali Catalyst

[0067] Referring to the method in Comparative Example 2 of EP0485613B1, 50 ml of isopropanol, 49.2 mmol of guaiacol and 49.2 mmol of sodium hydroxide were added to the reactor, stirred and mixed at 80°C, an isopropanol solution containing 24.6 mmol of formaldehyde was added to the reactor at room temperature, and the reaction was stirred at 50°C. According to high performance liquid chromatography analysis, the selectivity of 3-methoxy-4-hydroxybenzyl alcohol was 15.3%.

[0068] Comparative Example 2 Synthesis of Vanillyl Alcohol Using Zeolite Solid Base Catalyst

[0069] Referring to the method in Example 1 of CN1169766C, 5 g of zeolite catalyst and 1.6 mol of 37% formaldehyde aqueous solution were added to a 500 ml three-necked flask equipped with a mechanical stirring device, heated to 65° C., and then 0.09 mol of guaiacol was added. After reacting for 2 hours, liquid chromatography sampling and analysis showed that the conversion rate of guaiacol was 38%, and the selectivity of 3-methoxy-4-hydroxybenzyl alcohol was 55.3%.

[0070] Comparative Example 3: Synthesis of Vanillyl Alcohol Using Organic Base Catalyst

[0071] Referring to the method in Example 1 of patent CN101486630B, 0.1 mol of guaiacol, 20 ml of triethylamine, 0.4 mol of formaldehyde and 100 ml of water were added to a 500 ml three-necked flask equipped with a mechanical stirring device. The reaction mixture was heated to 30° C. in a constant temperature bath and kept constant. After the temperature was constant, the reaction time was controlled to be 4 hours. According to high performance liquid chromatography analysis, the conversion rate of guaiacol was 75.5%, and the selectivity of 3-methoxy-4-hydroxybenzyl alcohol was 25.3%.

[0072] The raw materials used in the experiment, lanthanum nitrate of guaiacol, cerium nitrate, terbium nitrate, copper nitrate, ammonia water, sodium hydroxide, ethylenediamine, zeolite, formaldehyde, and guaiacol are all chemical reagents.

[0073] In the present invention, the experimental raw material guaiacol, 3-methoxy-4-hydroxy-benzyl alcohol product and by-product are analyzed by liquid chromatography, and the chromatographic analysis conditions are polar chromatographic column, UV detector, detection wavelength of 310nm; column temperature of 40°C; flow rate of 0.4ml / min; injection volume of 5μL; and external standard method for quantification.

[0074] Acidity function of solid base catalyst H - Determination method according to literature: 0.1g of the dried solid base catalyst was immersed in 2mL of dry benzene in a small bottle, and 1 drop of 0.1% indicator benzene solution was added. After 12 hours, its color change was observed to determine its H -The indicator is 4-chloro-2-nitroaniline (pKa 17.2), 2,4-dinitroaniline (pKa 15.0), 2,4,6-trinitroaniline (pKa 12.2), phenolphthalein (pKa 9.3), etc. - The measurements were performed in an anaerobic environment.

[0075] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0076] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A composite metal oxide solid base catalyst, characterized in that: The composite metal oxide solid base catalyst is composited by amphoteric metal oxide copper oxide and common rare earth metal oxide, wherein the common rare earth metal oxide is one of La2O3, CeO2, Tb2O3, Dy2O3, Y2O3, Eu2O3 and Nd2O3, and can be used as a high-efficiency catalyst for catalyzing the synthesis of vanillin alcohol by the reaction of guaiacol and formaldehyde.

2. The composite metal oxide solid base catalyst according to claim 1, characterized in that The specific surface area of ​​the composite metal oxide solid base catalyst is 10-50m 2 / g; acid function H - is 9.3-15; the chemical composition is Re x O y nCuO, wherein n=1-10, x=1-2, y=2-3.

3. The composite metal oxide solid base catalyst according to claim 1, characterized in that Soluble rare earth metal salts and copper salts are co-precipitated into composite metal oxide solid base catalysts, and post-processed to increase their specific surface area to 10-50m 2 / g, acid function H - It is 9.3-15.

4. The composite metal oxide solid base catalyst according to claim 1, characterized in that The preparation method comprises the following steps: S1: Mix a 2 mol / L soluble copper salt aqueous solution and a soluble salt aqueous solution of a rare earth metal at a molar ratio of Re:Cu=1:1-10; the soluble copper salt is copper nitrate, copper chloride or copper acetate; the soluble rare earth metal salt is one of the nitrate, hydrochloride or acetate of La, Ce, Tb, Dy, Y, Eu or Nd; S2: adding 2-5 mol / L ammonia water to the mixed aqueous solution of soluble salts obtained in step S1 under stirring at room temperature to convert the soluble metal salts into a co-precipitation of hydroxides and oxides of copper metal and rare earth metal; S3: Separate the coprecipitate of metal hydroxide and oxide, wash with deionized water to remove the salt mixed in the coprecipitate of metal hydroxide and oxide, dry at 110-150°C, and then calcine and activate at 350-550°C for 0.5-2h to obtain a composite metal oxide solid base catalyst with a specific surface area of ​​10-50m 2 / g; acid function H - =9.3-15; chemical composition is Re x O y nCuO, n=1-10, x=1-2, y=2-3; based on Re, the molar yield of the preparation process is 95%-99%.

5. Use of the composite metal oxide solid base catalyst in the synthesis of vanillyl alcohol as claimed in any one of claims 1 to 3, characterized in that: The steps include: T1: adding 90%-95% ethanol solvent, raw material guaiacol and composite metal oxide solid base catalyst to the reactor respectively, controlling the mass of raw material guaiacol to be 5%-15% of the mass of ethanol solvent, so that raw material guaiacol and product vanillic alcohol can be completely dissolved at room temperature; controlling the mass of composite solid base catalyst to be 70%-150% of the mass of raw material guaiacol; T2: heating the reaction liquid to 60-79° C., adding a 37% formaldehyde aqueous solution under stirring, and controlling the feeding molar ratio to be: guaiacol: formaldehyde = 1: 0.9-1.2, so that guaiacol and formaldehyde are adsorbed on the surface of the composite solid base catalyst for hydroxymethylation reaction to generate 3-methoxy-4-hydroxybenzyl alcohol product and other by-products; T3: Keep the reaction warm for 2-6 hours. When the conversion rate of guaiacol in the reaction solution is greater than 95%, cool the reaction solution to room temperature, separate and recover the composite metal oxide solid base catalyst, wash the composite solid base catalyst with ethanol solvent, dry it at 110-150°C, and roast it at 350-550°C before recycling it; T4: vacuum distill the reaction liquid to recover 70%-90% of the volume of ethanol solvent for recycling; T5: cooling the distillation residue to 5-10°C, separating and crystallizing the crude vanillin alcohol product; T6: distilling the crude vanillic alcohol product under a vacuum degree of 1-3 mmHg to obtain a white refined vanillic alcohol product with a liquid chromatography content of 99.5%. The molar yield of the synthesis process is 60%-70% based on the guaiacol raw material.

Citation Information

Cited By

  • Bisphenol amine type antioxidant as well as preparation method and application thereof

    CN119874546A